ISLAM DAN SENI - Asy'ari, M. (Hunafa: Jurnal Studia Islamika, 2007)
Islam is a universal religion that regulates  relationship not only between mankind and God, between mankind and mankind but also between mankind and their soroundings.  It is within this context that moral teaching of the Qur’an and of prophet’s tradisition often become  references of  a Muslim’s deed, including his or her art expression. This article deals with Islam and art. In other words, to which extant does Islam permit a Muslim to perform an art.Kata Kunci : Islam, etika kesenian, seni estetika